The Qur'an and Mathematics: The Dimension of Tawhid and Knowledge in the Perspective of Afzalur Rahman - Aqdi Rofiq Asnawi; Muhammad Diaz Supandi; Fahmi Akhyar Al Farabi (Universitas Muhammadiyah Surakarta, 2026)
The relationship between the Qur'an and mathematics remains theoretically contested between two dominant approaches: historical-empirical studies that attribute mathematical development in Islamic civilization to intercultural transmission, and contemporary analyses focusing on numerical patterns within the Qur'anic text. While the former emphasizes external influences, the latter often risks numerological overinterpretation without a clear epistemological foundation. This study addresses this gap by reconstructing Afzalur Rahman's interpretation of the Qur'an-mathematics relationship within a tawḥīdic epistemological framework. Using qualitative library research and content analysis, this study examines Rahman's works in dialogue with Seyyed Hossein Nasr and Bediüzzaman Said Nursi. The findings show that Rahman conceptualizes mathematics as an expression of divine unity, where the number one symbolizes the origin and return of multiplicity. Mathematics is thus understood not merely as a quantitative discipline, but as an ethical and contemplative science integrating rational precision with spiritual consciousness. Furthermore, this framework contributes to contemporary Islamic education by fostering moral formation, strengthening epistemological coherence, and encouraging scientific creativity. However, Rahman's paradigm operates primarily as a normative-philosophical model rather than an empirical explanation of scientific development. This study contributes to debates on religion and science by clarifying the epistemological role of tawḥīd in knowledge integration.